2012
DOI: 10.1002/cjoc.201200183
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition Kinetics of High Impact Polystyrene/Organo Fe‐montmorillonite Nanocomposites

Abstract: In this article, high impact polystyrene/organo Fe-montmorillonite (HIPS/Fe-OMT) nanocomposites were prepared by melting intercalation. The thermal stability of HIPS/Fe-OMT nanocomposites increased significantly compared to that of HIPS examined in thermal degradation conditions. Kinetic evaluations were performed by Kissinger, Flynn-Wall-Ozawa, Friedman methods and multivariate nonlinear regression. Apparent kinetic parameters for the overall degradation were determined. The results showed that the activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In particular, two values for ABS (179.3 and 175.8 kJ mol À1 [28,47]) are only slightly lower than the average value of Keyb in Table 6, while other E a values found for pyrolysis of ABS depend remarkably on the heating rate considered [26], probably due to the method used (modelfitting) that sometimes may provide unreliable results [41]. Literature E a data on pyrolysis of virgin HIPS spread over a wide range, but the values determined by Liu and coworkers [27] agree well with those found in this study (within the estimated uncertainties). E a mean value for pyrolysis of PBT is slightly higher than literature ones [29,30] probably because of the presence of a high content of additives in the Black slot sample (Table 3).…”
Section: Kinetic Analysis Of Pyrolysismentioning
confidence: 83%
“…In particular, two values for ABS (179.3 and 175.8 kJ mol À1 [28,47]) are only slightly lower than the average value of Keyb in Table 6, while other E a values found for pyrolysis of ABS depend remarkably on the heating rate considered [26], probably due to the method used (modelfitting) that sometimes may provide unreliable results [41]. Literature E a data on pyrolysis of virgin HIPS spread over a wide range, but the values determined by Liu and coworkers [27] agree well with those found in this study (within the estimated uncertainties). E a mean value for pyrolysis of PBT is slightly higher than literature ones [29,30] probably because of the presence of a high content of additives in the Black slot sample (Table 3).…”
Section: Kinetic Analysis Of Pyrolysismentioning
confidence: 83%
“…In addition, a gas with a high caloric value may be used as fuel in the process and a solid residual stream, the char, useable as activated carbon or fillers. On the other hand, a remarkable amount of literature data can be collected from pyrolysis kinetics and thermal stability studies focused on single commercial or virgin polymers [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al used a glow-discharge plasma to modify the surface of biaxially oriented polypropylene (BOP) for biological use and studied the influence of various plasma parameters on its surface properties. They found that the hydrophilicity, active chemical functional groups and surface structure of the film were all significantly changed after plasma modification [7]. The induced modification of the surface was not permanent, since the surface tended to recover to its untreated state.…”
Section: Introductionmentioning
confidence: 99%